Female Education: an Undeniable Priority to Reduce Poverty: Empowering Women Through Education: A Path to Poverty Alleviation (Journal of Advances and Scholarly Researches in Allied Education, 2012)
Women constitute almost half of the population in theworld. But the hegemonic masculine ideology made them suffer a lot as they weredenied equal opportunities in different parts of the world. The rise offeminist ideas has, however, led to the tremendous improvement of women'scondition through out the world in recent times. Access to education has beenone of the most pressing demands of these women's rights movements. Women educationin India has also been a major preoccupation of both the government and civilsociety as educated women can play a very important role in the development ofthe country.